Palliative care: definition, importance and advances in Peru - Miranda-Chavez , Brayan (2023)
This review article addresses the concept, characteristics, steps for integration into the health system, and epidemiology of palliative care. Likewise, the advances and research carried out on palliative care in Peru are summarized. Palliative care can be defined as the active and holistic (comprehensive) care of people of all ages with severe health-related suffering due to serious illness and especially of those near the end of life. For this reason, it is important to understand that palliative care is not limited to the management of patients who have failed or no curative treatment. In Peru, although important advances have been made, there are still not enough services, training programs, or research groups in palliative care.